Safranal and its analogs inhibit Escherichia coli ATP synthase and cell growth - Liu, Mason (Int J Biol Macromol, 2016)
Safranal, a dominant component of saffron, is known to have antitumor, cytotoxic, and antibacterial properties. In this study, we examined safranal and its structural analogs— thymol, carvacrol, damascenone, cuminol, 2,6,6-Trimethyl-2-cyclohexene-1,4-dione (TMCHD), 4-Isopropylbenzyl bromide (IPBB), and 4-tert-Butylphenol (TBP) induced inhibition of Escherichia coli membrane bound F(1)F(o) ATP synthase. Safranal and its analogs inhibited wild-type enzyme to variable degrees. While safranal caused 100% inhibition of wild-type F(1)F(o) ATP synthase only, about 50% inhibition occurred for αR283D mutant ATP synthase. Moreover, safranal, thymol, carvacrol, damascenone, cuminol, TMCHD, IPBB, and TBP all fully abrogated the growth of wild-type E. coli cells and had partial or no effect on the growth of null and mutant E. coli strains. Therefore, the antimicrobial properties of safranal, thymol, carvacrol, damascenone, cuminol, TMCHD, IPBB, and TBP can be linked to their binding and inhibition of ATP synthase. Total loss of growth in wild-type and partial or no growth loss in null or mutant E. coli strains demonstrates that ATP synthase is a molecular target for safranal and its structural analogs. Partial inhibition of the αArg-283 mutant enzyme establishes that αArg-283 residue is required in the polyphenol binding pocket of ATP synthase for the binding of safranal. Furthermore, partial growth loss for the null and mutant strains in the presence of inhibitors also suggests the role of other targets and residues in the process of inhibition.